Professional Development Program Designed to Support Prospective Teachers' Enactment of Instructional Strategies to Differentiate Instruction for English Learners. Issue 1 (2nd January 2023) - Hinojosa, Denisse M.
Abstract: The increasing number of English learners (ELs) in U.S. public schools calls for teacher preparation programs to adequately prepare prospective teachers to meet the learning needs of ELs in general education classrooms, and to be culturally responsive to this growing population. This longitudinal study responds to the need to prepare prospective teachers to differentiate instruction for ELs in general education classrooms by sharing prospective teachers' interactions with representations of practice and approximations of practice throughout their participation in a professional development program. This draws attention on the ways in which prospective teachers reflected on the enactment of instructional strategies used in English as-a-second language settings to differentiate instruction for ELs. Finally, this study describes the ways in which working on cases with detailed descriptions of ELs prompted prospective teachers to develop habits of mind to differentiate instruction for ELs on a one-on-one basis, and to consider ELs' individual characteristics and learning needs.